Effect of earnings management on earnings predictability in information signaling perspective - Simamora, Alex Johanes (Fakultas Ekonomi dan Bisnis Universitas Tarumanagara, 2018)
This research is aimed to examine (1) effect of discretionary and innate accrual on earnings predictability (2) effect of market share and financial health on relationship between real earnings management and earnings predictability. This research use manufacture firms listed in Indonesian Stock Exchange 2003-2015 as research sample, with 2013-2014 as research period. Accrual earnings management is measured by discretionary and innate abnormal accrual. Real earnings management is measured by aggregate of abnormal cash flow of operation, abnormal production, abnormal discretionary expenses. As expected, discretionary accrual as opportunist act does not support earnings predictability, while innate accrual as information signaling of business model improves earnings predictability. Real earnings management as information signaling of market share and financial health improves earnings predictability as well. In general, earnings management as information signaling is more likely to communicate condition of firm and leads to informativeness of earnings.